2016
DOI: 10.1016/j.apenergy.2016.04.029
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of wind technology advancement on future global energy

Abstract: h i g h l i g h t sIntegrated assessment model perform a series of scenarios of technology advances. Explore the potential roles of wind energy technology advance in global energy. Technology advance impacts on energy consumption and global low carbon market. Technology advance influences on global energy security and stability. a r t i c l e i n f o b s t r a c tTo avoid additional global warming and environmental damage, energy systems need to rely on the use of low carbon technologies like wind energy. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 28 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…The existing literature has found that the size of the global (Marvel et al 2012) and U.S. (Lopez et al 2012) wind resource coupled with the increasing maturity of wind technology (Wiser et al 2011) might yield a robust role for wind energy (Barthelmie and Pryor 2014;Cochran et al 2014;IPCC 2014;Luderer et al 2014;Zhang et al 2016). Future wind deployment, however, can be strongly affected by the extent of continued wind energy cost reductions, the scale of greenhouse gas emission policies, competitiveness of other generation technologies, and other factors (IPCC 2014;Luderer et al 2014;Zhang et al 2016). Some of the scenario analysis literature focused specifically on future U.S. wind (MacDonald et al 2016, DOE 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature has found that the size of the global (Marvel et al 2012) and U.S. (Lopez et al 2012) wind resource coupled with the increasing maturity of wind technology (Wiser et al 2011) might yield a robust role for wind energy (Barthelmie and Pryor 2014;Cochran et al 2014;IPCC 2014;Luderer et al 2014;Zhang et al 2016). Future wind deployment, however, can be strongly affected by the extent of continued wind energy cost reductions, the scale of greenhouse gas emission policies, competitiveness of other generation technologies, and other factors (IPCC 2014;Luderer et al 2014;Zhang et al 2016). Some of the scenario analysis literature focused specifically on future U.S. wind (MacDonald et al 2016, DOE 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As costs fall, it was recorded that renewable energy markets continue to diversify geographically all over the world [10][11][12][13][14]. Europe remains an important market, as well as an innovation center, and also, activities continue to shift towards other regions with China again leading the world in new RE power capacity installations in 2018 [15][16][17][18][19][20]. As costs fall, it was recorded that renewable energy markets continue to diversify geographically all over the world [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The wind energy has been a main focus in the last decade particularly at offshore comparatively to other renewable sources. Up to the mid of 2016, 3, 344 offshore wind turbines with a combined capacity of 11, 538 MW have been installed in European waters [1,2].…”
Section: Introductionmentioning
confidence: 99%